Storytelling in luxury fashion - Sikarskie, Amanda Grace (Routledge, Taylor & Francis Group, 2021)
This book examines the ways in which luxury fashion brands use their heritage in their digital storytelling and marketing.With chapters from authors in China and Macau (PRC), India, Romania, Turkey, the United Kingdom, and the United States, covering British, Chinese, French, Japanese, Indian, Italian, and Turkish brands, this truly global collection is the first book of its kind devoted solely to the emerging study of digital heritage storytelling. This method of reaching potential consumers and perpetuating brand identity is a hugely important factor in the marketing of luxury brands and has yet to be studied comprehensively.The book will be of interest to scholars working in fashion studies, fashion history, design history, design studies, digital humanities, and fashion marketing.
9780367901288
Keywords: Aufsatzsammlung; America; blogs; branding; China; consumers; Dolce & Gabbana; digital humanities; economics; Fortnum & Mason; France; fashion; fashion history; fashion studies; Gucci; Hermes; House of Worth; haute couture; heritage; high-end; India; Instagram; Italy; Japan; Louboutin; luxe; luxury; marketing; narrative; price; Scotland; social media; storytelling; technology; United Kingdom; USA; websites; Youtube